Sweeping gas membrane evaporative cooling for the enhanced performance of vapour compression refrigeration - Smith, Benjamin D (University of Ottawa (Canada), 2010)
A sweeping gas membrane evaporative (SGME) cooling system was developed to remove heat from the condenser of a vapour compression chiller. The chiller was designed for hot environments and could only achieve a coefficient of performance (COP) of 1.0 using an air-cooled condenser. In this work, the condenser was modified to have circulating water absorb heat, which was then cooled in membrane modules by evaporation across a hydrophobic membrane into an air stream. Steady-state operation of the chiller was achieved with the SGME system. Increasing either air flow or water circulation rate increased the COP of the chiller, which reached a value of 1.83 with an optimal heat load of 435 W. The SGME system was then compared to cooling towers, a conventional method of evaporative heat removal. It was found that the SGME system provided more heat removal per unit volume and per unit of air flow than any investigated cooling tower. 89% of the heat removal was attributed to evaporation, and only 1.5% of the water entering the module was lost to evaporation, making the system more compact and efficient than towers. The sweeping gas membrane evaporation system was superior to both air-cooled condensers and to cooling towers.
Keywords: Engineering, Chemical.